Anxiety Level and Nurses' Work Motivation during the Covid-19 Pandemic - Hadi, Nurul Hadi; Apriani Susmita Sari; Sapwal, Muh. Jumaidi (Omni Nursing Journal, 2024)
Background: Nurses faced heightened psychological challenges during the COVID-19 pandemic, with anxiety emerging as a common response to increased workload, high-risk environments, and professional demands. Anxiety may diminish nurses' motivation to work effectively. Objective: This study aimed to determine the relationship between anxiety levels and the work motivation of nurses during the COVID-19 pandemic at Aikmel Public Health Center. Methods: The design study used a quantitative analytical observational with cross sectional approach. The number of samples was 50 respondents obtained by using the total sampling technique. The questionnaire used in this research was the Hamilton Anxiety Rating Scale (HARS) and Multidimensional Work Motivation Scale (MWMS). Statistical analysis used the Spearman Rank test with a 95% confidence level (α = 0.05). Results: Most nurses experienced moderate anxiety, as many as 28 people (56.0%) and most nurses had good motivation as many as 29 people (58.0%). Statistical analysis showed a significant correlation between anxiety levels and work motivation (r = 0.376; p = 0.007). Conclusion: There is a significant relationship between anxiety levels and nurses' work motivation during the COVID-19 pandemic. Lower anxiety levels are associated with higher motivation, suggesting the importance of psychological support for nurses in crisis situations.